Sleep Quality Mediates the Association Between Cerebral Small Vessel Disease Burden and Frailty: A Community-Based Study - Zhao, Jing; Qu, Wensheng; Zhou, Xirui; Guo, Yinping; Zhang, Yi; Wu, Lingshan; Yu, Zhiyuan; Huang, Hao; Luo, Xiang (Frontiers in Aging Neuroscience, 2021)
Abstract Background: Physical frailty is a common problem among older adults which usually leads to adverse health outcomes. The imaging markers of cerebral small vessel disease (CSVD) are associated with frailty, but the underlying mechanisms remain unclear. The present study aimed to investigate the mediating role of sleep quality in the relationship between CSVD burden and frailty. Methods: We performed a cross-sectional study and enrolled community residents. Frailty and sleep quality were measured using the Fried frailty phenotype and the Pittsburgh Sleep Quality Index (PSQI), respectively. A multivariate linear regression analysis and a Bootstrap analysis were performed to examine the association among the key variables and the mediating role of sleep quality. Results: Of the 726 participants (mean age: 65.5 ± 6.5 years, 59.8% female), the numbers (percentages) of the frail, prefrail, and robust residents were 49 (6.7%), 310 (42.7%), and 367 (50.6%), respectively. After adjusting for covariates, the CSVD burden and PSQI score were significantly associated with the frailty score. In addition, sleep quality played a partial mediating role in the association between CSVD burden and physical frailty. The mediating effect was 21.9%. Conclusion: The present study suggests that sleep quality is a mediator of this association between CSVD and frailty in community-dwelling older adults. Improving sleep quality might be helpful to mitigate the risk of frailty in CSVD patients.